Methodological Variation in Empirical Corporate Finance - Mitton, Todd (Review of Financial Studies, 2022)
Abstract I document large variation in empirical methodology in corporate finance regressions in top finance journals. Although methodological variation allows for customization of empirical tests to fit specific theories, it can also enable excessive reporting of statistically significant results. For example, given discretion over 10 routine methodological decisions, a researcher could report that over 70% of randomly generated variables are statistically significant determinants of leverage at the 5% level. The methodological decisions that affect statistical significance the most are dependent variable selection, variable transformation, and outlier treatment. I discuss remedies that can mitigate the negative effects of methodological variation.